Optimal capacitor allocation for minimizing cost of energy loss in active distribution network with different load levels - Mya Myintzu; Kyaw Myo Lin; Khine Zin Oo (Institute of Advanced Engineering and Science, 2023)
This paper proposes an effective technique to allocate a shunt capacitor using a meta-heuristic optimization-approach for minimizing the cost of energy losses. Particle swarm optimization (PSO) algorithm incorporated with MATPOWER is trained for minimizing the targeted function of the optical capacitor placement problem. The 115-node active distribution network supplied by MESC in the Mandalay distribution area is applied as a scenario. The results including active power loss and system energy loss, size and location of the optimized capacitor, voltage profiles, and the cost of energy loss are attained and analyzed. The simulations results revealed that the optimal allocation of the capacitor provides a significant reduction in the cost of energy losses as well as improvement in voltage profile with compensation of reactive power.